Implementasi Manajemen Bandwidth Menggunakan Metode Queue Tree Pada Jaringan Internet - MUSMUHARAM .; Cosmas Eko Suharyanto (Informatika Universitas Siliwangi, 2020)
SMKN 5 Batam City is an educational institution located in Kavling Bukit Kamboja, Sungai Pelunggut, Kec, Sagulung, Batam City, Riau Islands. The availability of network infrastructure to be institutionalized by education will expedite the educational process including internet network services at SMKN 5 Batam City. The networks used in SMKN 5 Kota Batam are the Local Area Network (LAN) and Wireless Local Area Network (WLAN). Batam City Vocational School 5 has 82 PCs (Personal Computers) connected to the network and Access Points as access to the hotspot network, which uses an indie home ISP with a bandwidth capacity of 100Mbps and 5Mbps using an astinet ISP. Problems that occur on the internet network at SMKN 5 Kota Batam, do not yet have an allocation of bandwidth distribution for network users, causing unstable and uninterrupted network access. Therefore there must be proper bandwidth management controls, implementing bandwidth management and optimizing security authentication. So that the available bandwidth can be used fairly, by applying the queue method. And from the tests carried out, authentication of security and bandwidth management using the tree queue method, fair and even bandwidth can be used as well as the tree queue method proven to be able to use bandwidth both for downloading and downloading. uploaded.